Effect of Clomethiazole Vs. Clorazepate on Hepatic Fat and Serum Transaminase Activities in Alcohol-Associated Liver Disease: Results from a Randomized, Controlled Phase II Clinical Trial. (22nd December 2022) - Hohmann, Nicolas; Schröder, Fabian; Moreira, Bernardo; Teng, Haidong; Burhenne, Jürgen; Bruckner, Thomas; Mueller, Sebastian; Haefeli, Walter E; Seitz, Helmut K
Abstract: Aims: Alcohol-associated liver disease (ALD) is a global health problem caused, among other factors, by oxidative stress from the formation of reactive oxygen species (ROS). One important source of ROS is microsomal ethanol metabolism catalyzed by cytochrome P450 2E1 (CYP2E1), which is induced by chronic ethanol consumption. Inhibition of CYP2E1 by clomethiazole (CMZ) decreases oxidative stress in cell cultures and improves ALD in animal studies. Our study aimed to assess the benefits of a CYP2E1 inhibitor (clomethiazole) in detoxification of patients with ALD. Methods: Open label, randomized controlled clinical trial to study whether CYP2E1 inhibition improves ALD in the patients with alcohol use disorders admitted for alcohol detoxification therapy (ADT). Patients had to have a serum aspartate aminotransferase (AST) activity exceeding twice the upper normal limit at time of admission and be non-cirrhotic defined by fibroscan value <12 kPa. Sixty patients were randomly assigned to ADT with either CMZ or clorazepate (CZP) for 7–10 days in a 1:1 ratio. The chlorzoxazone test of CYP2E1 activity was performed at enrolment and at 2 points during the study. Results: ADT improved hepatic steatosis (controlled attenuation parameter) in both groups significantly. A trend towards a greater improvement in hepatic fat content during ADT (−21.5%) was observed in the CMZ group (252 ± 48 dB/m vs. 321 ± 38 dB/m; P < 0.0001) compared with the CZP group (−13.9%; 273 ± 38 dB/m vs. 317 ± 39 dB/m; P < 0.0001). As already reported, serum AST ( P < 0.004) and alanine aminotransferase (ALT) activities ( P < 0.0006) significantly decreased in CMZ patients as compared with patients on CZP by the end of hospitalization. A significant correlation was found between AST ( P = 0.023), ALT ( P = 0.009), GGT ( P = 0.039) and CAP. Conclusion: This study demonstrates that CMZ improves clinical biomarkers for ALD in humans most likely due to its inhibitory effect on CYP2E1. Because of its addictive potential, CMZ can only be given for a short period of time and therefore other CYP2E1 inhibitors to treat ALD are needed.